APLIKASI PEMBELAJARAN BERMAIN ALAT MUSIK GITAR UNTUK PEMULA BERBASIS ANDROID - Sihombing, Adelbert Farlind; Karnadi, Very (Computer Science and Industrial Engineering, 2020)
Playing guitar is one of the activities that many people are interested in. If the lack of time learning in theory and practice can make students become difficult in learning so they can’t improve their abilities in playing guitar. along development of technology, it is needed an Android based learning application that is easy to use which can be used at home or in the school. In this research researchers use the Rapid Application Development (RAD) and Unified Modelling Language (UML) methods as designing models and designing this learning application using the Eclipse IDE application. The app contains information about the guitar, the simulation of the chord and audio in each chord, the theory of the chord conversion, and some of the songs accompanied by a chord in the lyrics. Based on the test results using Black-box testing techniques showed that the application went well.